Effectiveness of Cassava Harvesting by Applying Harvesting Implement - Warji, Warji; Asmara, Sandi; Hidayat, Kuswanta Futas; Sanjaya, Purba; Endaryanto, Teguh (Jurnal Agricultural Biosystem Engineering, 2025)
Cassava is one of Indonesia’s leading food commodities, especially in Lampung Province. However, cassava harvesting is still predominantly done manually, which is time-consuming, labor-intensive, and prone to crop damage. This study aims to evaluate the effectiveness of cassava harvesting using a Kubota mechanical harvesting implement compared to traditional manual methods. The research was conducted in Bandar Mataram District, Central Lampung Regency, over an area of 0.75 hectares and observed parameters including harvest time, tuber damage, losses, and labor efficiency. Results showed that the harvesting implement significantly improved efficiency, allowing one machine to harvest up to 1.07 hectares per day, compared to only 0.045 hectares per day per person using manual labor. Tuber damage and losses were also reduced from 7% in manual harvesting to 1.59% with the implement. Furthermore, the implement created soil ridges suitable for direct replanting without further tillage. Despite its advantages, some operational weaknesses were identified, such as the need for stem cutting and transportation improvements. Overall, the use of mechanized harvesting tools enhances cassava farming efficiency and has the potential to reduce labor dependency and improve farmer productivity.